Large anatomical changes in head-and-neck cancers – A dosimetric comparison of online and offline adaptive proton therapy. (May 2023) - Bobić, Mislav; Lalonde, Arthur; Nesteruk, Konrad P.; Lee, Hoyeon; Nenoff, Lena; Gorissen, Bram L.; Bertolet, Alejandro; Busse, Paul M.; Chan, Annie W.; Winey, Brian A.; Sharp, Gregory C.; Verburg, Joost M.; et al.
Highlights: Daily online adaptation improves target coverage over offline replanning despite smaller margins. Due to smaller target margins, daily online adaptation lowers the dose to healthy tissue. Online adaptation with a simple beamlet-weight tuning technique proved sufficient for head-and-neck patients with large anatomical changes. Abstract: Purpose: This work evaluates an online adaptive (OA) workflow for head-and-neck (H&N) intensity-modulated proton therapy (IMPT) and compares it with full offline replanning (FOR) in patients with large anatomical changes. Methods: IMPT treatment plans are created retrospectively for a cohort of eight H&N cancer patients that previously required replanning during the course of treatment due to large anatomical changes. Daily cone-beam CTs (CBCT) are acquired and corrected for scatter, resulting in 253 analyzed fractions. To simulate the FOR workflow, nominal plans are created on the planning-CT and delivered until a repeated-CT is acquired; at this point, a new plan is created on the repeated-CT. To simulate the OA workflow, nominal plans are created on the planning-CT and adapted at each fraction using a simple beamlet weight-tuning technique. Dose distributions are calculated on the CBCTs with Monte Carlo for both delivery methods. The total treatment dose is accumulated on the planning-CT. Results: Daily OA improved target coverage compared to FOR despite using smaller target margins. In the high-risk CTV, the median D98 degradation was 1.1 % and 2.1 % for OA and FOR, respectively. In the low-risk CTV, the same metrics yield 1.3 % and 5.2 % for OA and FOR, respectively. Smaller setup margins of OA reduced the dose to all OARs, which was most relevant for the parotid glands. Conclusion: Daily OA can maintain prescription doses and constraints over the course of fractionated treatment, even in cases of large anatomical changes, reducing the necessity for manual replanning in H&N IMPT.